Some boundary value problems for the Cauchy-Riemann equation in half lens - Taghizadeh, Nasir; Soltani Mohammadi, Vahid (Eurasian Mathematical Journal, 2018)
In this article, the boundary behaviour of the Schwarz-type operator on the half lens Ω will be discussed and the existence of boundary values at corner points is proved. Finally, two basic boundary value problems, namely, Dirichlet and Neumann problems for analytic functions and more generally the Dirichlet problem for the inhomogeneous Cauchy-Riemann equation in Ω is investigated.